TREATMENT OF COVID-19 WITH CASIRIVIMAB/INDEVIMAB IN A PATIENT WITH CERVICAL SPINE INJURY: A CASE REPORT - Vrhovac, Miljana; Stanišić, Tijana; Mirković, Milan; Veličković, Jelena; Dalifi, Sead; Jeremić, Danilo; Pilipović, Filip; Adžić-Vukičević , Tatjana (Srpski medicinski časopis Lekarske komore, 2025)
Introduction/Aim: We present a patient suffering from COVID-19 with a cervical spine injury who was treated with the antiviral drug casirivimab/indevimab (Regen-CoV), monoclonal antibodies for COVID-19, during hospital treatment at the Batajnica Hospital of the University Clinical Center of Serbia. Case report: The administration of the drug casirivimab/indevimab (Regen-CoV) prevented the development of a more severe picture of Covid-19 and led to the rapid negativization of the nasopharyngeal swab for SARS-CoV-2 in our patient who had a cervical spine injury. The patient underwent successful cervical spine surgery at the Institute for Orthopedic-Surgical Diseases in Banjica, which led to the recovery of the neurological deficits he had previously. Conclusion: We showed another significant indication for using casirivimab/indevimab (Regen-CoV) in hospital conditions, which was off-label according to therapeutic protocols.